Front Cover: Structure‐Activity Relationships of Benzamides and Isoindolines Designed as SARS‐CoV Protease Inhibitors Effective against SARS‐CoV‐2 (2/2021). (22nd January 2021) - Welker, Armin; Kersten, Christian; Müller, Christin; Madhugiri, Ramakanth; Zimmer, Collin; Müller, Patrick; Zimmermann, Robert; Hammerschmidt, Stefan; Maus, Hannah; Ziebuhr, John; Sotriffer, Christoph; Schirmeister, Tanja
Abstract : The Front Cover presents an experimental weapon changing the outcome of a battle in the respiratory system. The picture shows severe acute respiratory syndrome corona virus (SARS‐CoV) particles and the virus′ own papain‐like protease (PL pro, PDB‐ID 3E9S) through the window of a cockpit. The essential protease is targeted and "bombarded" with the novel inhibitors shown on the screens. Hitting the protease leads to the destruction of the viruses. The corresponding article describes inhibitors developed for SARS‐CoV PL pro and examines the transferability of their effectiveness to the close homologue of SARS‐CoV‐2. More information can be found in the Full Paper by Tanja Schirmeister et al. . Cover designed by Hannah and Lea Maus.